Comprehensive Risk Assessment of Applying Biogas Slurry in Peanut Cultivation - Liu, Qingyu; Zhao, Zixuan; Xue, Zhiping; Li, Ding; Wen, Zhining; Ran, Yi; Mei, Zili; He, Li (Frontiers in Nutrition, 2021)
Biogas slurry, a byproduct of biogas plants, is considered a high-quality bio-organic fertilizer. Despite providing nutrients for crops, biogas slurry may contain high concentration of heavy metals leading to food safety problems and endangering human health if such metals are absorbed by the plants. Therefore, biogas slurry should undergo systematic risk assessment prior to direct use on farm lands to ensure its safety for soils and crops. In this study, the risk of applying biogas slurry in peanuts cultivation was comprehensively evaluated. To the best of our knowledge, it is the first time for the risk assessment of biogas slurry in peanut cultivation. According to nitrogen contents, different concentrations of biogas slurry were applied for peanut cultivation. The results showed that the content of As and Hg in the soil increased significantly. Hence, after applying biogas slurry, the potential ecological risk of the soil was found to be high. The contents of Cu, Zn, Pb, Cd, and As in peanut kernel samples under different levels of biogas slurry application were all lower than the maximum limit set by the Standardization Administration of China. Meanwhile the contents of Hg were all higher than the maximum limit. The long-term consumption of peanuts grown with such high dosage of biogas slurry would cause harm to the health of children aged 2~6 years with high consumption level.